Efficacy of oleandrin and PBI-05204 against viruses of importance to commercial pig health management - Newman, Robert A.; Abdelsalam, Karim; Buterbaugh, Robin; Sastry, K. Jagannadha (Frontiers in Animal Science, 2024)
Background: Infec on by porcine respiratory and reproduc ve syncy al virus (PRRSV), swine influenza virus (SIV) and porcine epidemic diarrhea (PEDV) adversely affect worldwide pig produc on. Because effec ve control remains elusive the present research was designed to explore the in vitro an viral ac vity of oleandrin and an N. oleander extract (PBI-05204) against each porcine virus.Methods: Monkey kidney (MARK-145) cells, Madin-Darby canine kidney cells (MDCK), and African green monkey kidney cells (VERO 76) were used for in vitro culture systems for PRRSV, SIV and PEDV, respec vely. Cytotoxicity was established using serial dilu ons of oleandrin or PBI-05204. Noncytotoxic concentra ons of each product were used either prior to or at 12 h and 24 h following exposure to corresponding viruses. Infec ous virus ters were also determined.Results: Oleandrin and PBI-05204 demonstrated strong an viral ac vity against PRRSV, SIV and PEDV when added prior to or following infec on of cells. Determina on of viral loads by PCR demonstrated a decline in PRRSV replica on reaching 99.57% and 99.79% for oleandrin and PBI-05204, respec vely, and decrease of 95.36% and 99.54% in infec vity of progeny virus in PRRSV infected cultures. Similarly, oleandrin tested against SIV and PEDV was effec ve in near complete inhibi on of infec ous virus produc on.The research demonstrates the potency of oleandrin and PBI-05204 to inhibit infec vity of three important porcine viruses. These data showing non-toxic concentra ons of oleandrin as a single common agent for inhibi ng infec vity of the three different porcine viruses tested here support further inves ga on of an viral efficacy and possible in vivo use. Keywords PBI-05204, oleandrin, Nerium oleander, porcine reproduc ve and respiratory syncy al virus, swine influenza virus, porcine epidemic diarrhea virusInfec ous diseases represent a global threat to humans, livestock, and wildlife animals with poten al cross-species transmission. 1,2 Over the last 30 years, diseases caused by emerging swine viruses have acquired par cular relevance, ORCID iD Robert A. Newman h ps://orcid.org/0000-000105661-5846 K Jagannadha Sastry h ps://orcid.